COST-EFFECTIVENESS ANALYSIS OF AMLODIPINE AND CANDESARTAN USE IN TYPE 2 DIABETES MELLITUS PATIENTS WITH COMORBID HYPERTENSION IN YOGYAKARTA, INDONESIA - Hadning, Ingenida; Riswana, Nabila Uswah; Ardhani, Nariswari Cahya; Arini, Merita (Jurnal Farmasi Sains dan Praktis, 2025)
Type 2 diabetes mellitus, often accompanied by comorbid hypertension, necessitates expensive and prolonged treatment. Therefore, conducting a cost-effectiveness analysis is crucial to identify the most economically viable option by comparing the costs and therapeutic efficacy of amlodipine and candesartan in patients with type 2 diabetes mellitus and comorbid hypertension in Yogyakarta, Indonesia. This research aims to analyze therapy costs and effectiveness using pharmacoeconomic assessment, specifically calculating ACER (Average Cost-Effectiveness Ratio) and ICER (Incremental Cost-Effectiveness Ratio) values. The study uses a quantitative approach with retrospective data collection from patient medical records through total sampling. This research gathered data from 149 medical records. The cost-effectiveness analysis based on ACER values revealed the following: amlodipine 5 mg cost IDR 86; amlodipine 10 mg cost IDR 51; candesartan 8 mg cost IDR 571; candesartan 16 mg cost IDR 727. The ICER value of amlodipine 5 mg – candesartan 8 mg cost IDR 1,527; amlodipine 5 mg – candesartan 16 mg cost IDR 2,192; amlodipine 10 mg – candesartan 8 mg cost IDR –8454; amlodipin 10 mg – candesartan 16 mg cost IDR –5,979. The therapy is considered cost-effective when the ACER value is low, and the negative value of ICER indicates that the treatment has lower costs with greater effectiveness. So, using amlodipine 10 mg is the most cost-effective approach for reducing blood pressure in type 2 diabetes mellitus patients with comorbid hypertension in Yogyakarta, Indonesia.